ANALISIS BUDAYA KESELAMATAN PASIEN DENGAN PENDEKATAN INSTITUTE FOR HEALTHCARE IMPROVEMENT DITINJAU DARI ASPEK ORGANISASI DI RUMAH SAKIT JIWA DAERAH DR AMINO GONDOHUTOMO SEMARANG TAHUN 2016 - Helena Napitupulu; Sudiro Sudiro; Eka Yunila Fatmasari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Division of works TKPRS still not detailed, coordination is still not running well. there are some events that happen again, less commitment in studying the incident, training is not given to all of the staff. The approach of Institute For Healthcare Improvement needs to be done to build a culture of patient safety. The research methods using qualitative methods. Data obtained from a document review and in-depth interviews. Informant as many as ten people consist of TKPRS members, chairman of the quality committee, deputy director of medical services, head space UPIP dan nurses. Data is presented in narrative form and matrix interview. The results showed hospital had designed a patient safety team but the Division of works TKPRS still not detailed. there is no delegation of authority and coordination have not been going well. The hospital has not formed an adverse event response team. In creating a reporting system, TKPRS has had a divisions of work , but delegation of authority and coordination has not gone well. In building the patient safety culture, focus studied the error system, not given punishment and reward for the reporter, follow-up and analysis of patient safety incident reports but still not optimal. TKPRS expected to provide simulation and patient safety training to all staff, provide rewards for the reporter, held a meeting one time in a week, monitoring the implementation of the tasks and activities, held a briefing staf and sharing experience.